PKS 2332–017 and PMN J1916–1519: Candidate Blazar Counterparts to Two High-energy Neutrino Events - Shunhao Ji; Zhongxiang Wang; Dong Zheng (The Astrophysical Journal)
We report our counterpart identification study for two high-energy neutrino events IC-130127A and IC-131204A listed in the IceCube Event Catalog of Alert Tracks. These two events belong to Gold alerts, which have a significant probability of being of astrophysical origin. Within the events’ 90% positional uncertainty regions, we, respectively, find PKS 2332–017 and PMN J1916–1519. The first source is a flat-spectrum radio quasar at redshift z = 1.18, and the second is a blazar of an uncertain type with photometric z = 0.968. As they correspondingly had a γ -ray flare temporally coincident with the arrival times of IC-130127A and IC-131204A, we identify them as the respective neutrino emitters. Detailed analysis of the γ -ray data for the two blazars, obtained with the Large Area Telescope onboard the Fermi Gamma-ray Space Telescope, is conducted. The two flares, respectively, from PKS 2332–017 and PMN J1916–1519 lasted ~4 yr and ~4 months and showed possible emission hardening by containing high-energy ~2–10 GeV photons in the emissions. Accompanying the flare of PKS 2332–017, optical and mid-infrared brightening variations were also observed. We discuss the properties of the two sources and compare the properties with those of the previously reported (candidate) neutrino-emitting blazars.